Smart Circular Economy in healthcare – An introduction to the 9R framework - Bühler Lydia; Fendt Daniela; Wittenberg Thomas; Hamper Andreas (Current Directions in Biomedical Engineering)
This contribution examines the concept of circular economy (CE) within the healthcare sector, introducing the 9R paradigm as a novel framework for the implementation of sustainable strategies. Given the significant CO2 emissions from the medical device sector and the heterogeneous digitalization across the industry, CE offers an avenue to minimize environmental impact while simultaneously enhancing patient care. Leveraging advanced data platforms and digital technology can help reduce resource waste and CO2 emissions, while also optimizing patient care by avoiding redundant diagnostics and treatments. The contribution provides a brief introduction for the application of the 9R paradigm in the healthcare sector and highlights the opportunities associated with the implementation of CE strategies. It outlines innovative data-driven business models based on CE and digital transformation principles. In conclusion, the strategic application of R-strategies can be described as a multi-layered approach requiring close collaboration among all stakeholders to shape a more sustainable and efficient future in healthcare and provide new digital business models.